Tính:
a)5a2xy-10a3x-15axy
b)(2x+3).(3-2x)-(2x+1)2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(5a^2xy-10a^3x-15axy\)
\(=5ax\left(ay-2a^2-3y\right)\)
b: \(\left(3+2x\right)\left(3-2x\right)-\left(2x+1\right)^2\)
\(=9-4x^2-4x^2-4x-1\)
\(=-8x^2-4x+8\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,=9x^2+12x+4-18x-4+10x^2=19x^2-6x\\ b,=8x^3-27-8x^3-36x^2-54x-27=-36x^2-54x-54\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 5:
a. 1 - 2y + y2
= (1 - y)2
b. (x + 1)2 - 25
= (x + 1)2 - 52
= (x + 1 - 5)(x + 1 + 5)
= (x - 4)(x + 6)
c. 1 - 4x2
= 12 - (2x)2
= (1 - 2x)(1 + 2x)
d. 8 - 27x3
= 23 - (3x)3
= (2 - 3x)(4 + 6x + 9x2)
e. (đề hơi khó hiểu ''x3'' !?)
g. x3 + 8y3
= (x + 2y)(x2 - 2xy + y2)
![](https://rs.olm.vn/images/avt/0.png?1311)
c: \(=\dfrac{2\left(x+3\right)}{x\left(3x-1\right)}\cdot\dfrac{-\left(3x-1\right)}{x\left(x+3\right)}=\dfrac{-2}{x^2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
\(a,=6x^2+6x\\ b,=15x^3-10x^2+5x\\ c,=6x^3+12x^2\\ d,=15x^4+20x^3-5x^2\\ e,=2x^2+3x-2x-3=2x^2+x-3\\ f,=3x^2-5x+6x-10=3x^2+x-10\)
Bài 2:
\(a,\Leftrightarrow3x^2+3x-3x^2=6\\ \Leftrightarrow3x=6\Leftrightarrow x=2\\ b,\Leftrightarrow6x^2+3x-6x^2+9x-2x-3=10\\ \Leftrightarrow10x=13\Leftrightarrow x=\dfrac{13}{10}\)
\(a,5a^2xy-10a^3x-10axy=5ax\left(ay-2a^2-2y\right)\)
\(b,\left(2x+3\right)\left(3-2x\right)-\left(2x+1\right)^2\\ =-\left(4x^2-9\right)-\left(4x^2+4x+1\right)\\ =-4x^2+9-4x^2-4x-1\\ =-8x^2-4x+8\\ =-4\left(2x^2+x-2\right)\)